The Impact of Palliative Care to Improve Quality of Life Patient with Hepatocellular Carcinoma - Rahmi, Anggun Hidayatur; Syarifudin, Muhammad (Indonesian Academia Health Sciences Journal, 2021)
Introduction: Palliative care, specialized interdisciplinary care that focuses on quality of life while living with a serious illness, has the potential to offer additional support in patients with HCC and their families as they navigate life with the disease. Aim: This Systematic review was aimed to Palliative Care to Improve Quality of Life Patient with Hepatocellular Carcinoma. Method: Literature search is through Scopus, Pubmed, Proquest, Science Direct, and SAGE with the last 5 years (2014-2019). Result: There were 15 selected journals from 2493 journal articles found. Conclusion: Palliative care given as early as possible can improve the quality of life of patients, so patients can live longer, compared with patients who only seek treatment without being given palliative therapy.